2021
DOI: 10.1177/09544119211022985
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of stress distributions at the implant-abutment complex and peri-implant bone around mandibular dental implants with different neck geometries and inclinations

Abstract: This study aimed to investigate the effects of the different dental implant neck designs, diameters, and inclinations, on the stress distributions at the mandibular crestal bone and implant-abutment complex, using three-dimensional (3D) finite element stress analysis (FEA) method. Finite element models of three-unit fixed partial dentures supported with two same length implants (10 mm), placed on the second premolar and second molar regions, were designed. Eight different models were designed according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In contrast to the similar stress distributions observed throughout the model, even with different crown materials, differences were observed in the stress distribution in the crown‐abutment junction area. Local stress accumulation was detected in the junction regions in vertical (100N 26 and 300N 27 ) and oblique (150N 28 ) loading conditions. Various loading conditions are useful to identify the different stress modes under complex loading situations in oral environment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the similar stress distributions observed throughout the model, even with different crown materials, differences were observed in the stress distribution in the crown‐abutment junction area. Local stress accumulation was detected in the junction regions in vertical (100N 26 and 300N 27 ) and oblique (150N 28 ) loading conditions. Various loading conditions are useful to identify the different stress modes under complex loading situations in oral environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is a method used to analyse stresses and strains in complex mechanical systems [23], which has been widely used to study a number of dental biological research questions. In implantology, FEA has been used to evaluate the stress distributions at the implant-abutment complex and in the peri-implant bone around implants of different designs [24,25]. In prosthodontics, FEA has been used to evaluate the mechanical behaviour of different prosthetic solutions [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Maximum stress areas may be located at the implant neck, and possible overloading could occur in the form compression in the compact bone (due to lateral components of the occlusal load) and in the form tension at the interface between cortical and trabecular bone (due to vertical intrusive loading components) [93-95.]. Load transmission may also occur in the abutment-implant interface zone, which may also lead to the above mentioned phenomenon [96][97][98]. Our FEA analyses also confirmed that the implant-abutment connection greatly influences the distribution of forces in different ways at different heights between the implant and the bone.…”
Section: Discussionmentioning
confidence: 99%